Evaluating the primary yield limiting leaf nutrient deficiency of coconut (Cocos nucifera Linn.) in a major coconut growing zone of Tamil Nadu - V.P. Duraisami, V. Selvamani and (Journal of Plantation Crops, 2018)
The present study was conducted to evaluate the yield relationship of leaf nutrient status in two major coconut growing districts (Coimbatore and Tiruppur) of Tamil Nadu. Leaf samples and yield data were collected from coconut gardens and the nutrient contents were analysed. Leaf nitrogen, phosphorus and potassium status in the study area ranged between 0.71 to 2.63, 0.05 to 0.15 and 0.51 to 1.76 per cent with a means of 1.42, 0.11 and 0.99 per cent, respectively. The leaf calcium, magnesium and sulphur contents were in the range of 0.54 to 1.92, 0.11 to 1.51 and 0.16 to 2.14 per cent with the mean values of 0.88, 0.48 and 0.62 per cent, respectively. The leaf micronutrient status were in the range between 37 to 392 mg kg-1 of Fe, 158 to 634 mg kg-1 of Mn, 6.6 to 40.7 mg kg-1 of Zn, 2.0 to 54.8 mg kg-1 of Cu and 3.2 to 23.8 mg kg-1 of B. The mean values of Fe, Mn, Zn, Cu and B were 230.7, 315, 19.3, 10.8 and 12.6 mg kg-1 respectively. Significant and positive correlation coefficient was observed between yield with leaf magnesium (0.269**), nitrogen (0.260**) and potassium (0.200**). Stepwise multiple regression analysis revealed that leaf potassium, nitrogen and magnesium are the most important yield influencing leaf nutrients in the study area.